Baohuoside-I suppresses cell proliferation and migration by up-regulating miR-144 in melanoma - Ya-Guang Peng (Pharmaceutical Biology, 2018)
Context: Baohuoside-I was reported to induce apoptosis in non-small-cell lung cancer and inhibit the growth of multiple myeloma cells. The antitumour potential of baohuoside-I has not been demonstrated in melanoma yet. Objective: To investigate the potential antitumour activity of baohuoside-I against melanoma and elucidate its underlying molecular mechanism. Materials and methods: Cell viability was evaluated by MTT assay. The malignant invasion capacity was measured with trans-well assay. The relative expression change of microRNAs was profiled with microarray. TargetScan was utilized for prediction of target gene of miR-144. Regulatory effect of miR-144 on SMAD1 was determined by dual luciferase reporter assay. Endogenous SMAD1 protein in response to ectopic expression of miR-144 was determined by immunoblotting. Xenograft mice were employed to evaluate antitumour potential of baohuoside-I (25 mg/kg by tail intravenous injection every two days) in vivo. Results: Baohuoside-I significantly inhibited proliferation (45 ± 4% reduction in M14 and 35 ± 3% reduction in MV3 at 24 h) and migration (70 ± 4% reduction in M14 and 72 ± 3% reduction in MV3) in melanoma cells. Mechanistically, baohuoside-I up-regulated miR-144 expression levels (3 ± 0.2-fold). Silence of miR-144 reversed the inhibition of baohuoside-I in melanoma. We have identified that SMAD1 was the novel target of miR-144. Moreover, baohuoside-I suppressed melanoma in vivo (52 ± 8% reduction in xenograft tumour size at day 20). Conclusions: Our data suggested significant antitumour potential of baohuoside-I against melanoma both in vitro and in vivo, which warrants further laboratory investigation and clinical trial.